Longevity pattern in the Italian region of Emilia Romagna: a dynamic perspective - Giulia Roli; Alessandra Samoggia; Rossella Miglio; Rosella Rettaroli (Geospatial Health, 2012)
The pattern of longevity in the Italian north-eastern region of Emilia Romagna was investigated at the municipality level, considering a modified version of the centenarian rate (CR) in two different periods (1995-1999 and 2005-2009). Due to the rareness of such events in small areas, spatio-temporal modelling was used to tackle the random variations in the occurrence of long-lived individuals. This approach allowed us to exploit the spatial proximity to smooth the observed data, as well as controlling for the effects of a set of covariates. As a result, clusters of areas characterised by extreme indexes of longevity could be identified and the temporal evolution of the phenomenon depicted. A persistence of areas of lower and higher occurrences of long-lived subjects was observed across time. In particular, mean and median values higher than the regional ones, showed up in areas belonging to the provinces of Ravenna and Forli-Cesena, on one side spreading out along the Adriatic coast and, on the other stretching into the Apennine municipalities of Bologna and Modena. Further, a longitudinal perspective was added by carrying out a spatial analysis including the territorial patterns of past mortality. We evaluated the effects of the structure of mortality on the cohort of long-lived subjects in the second period. The major causes of death were considered in order to deepen the analysis of the observed geographical differences. The circulatory diseases seem to mostly affect the presence of long-lived individuals and a prominent effect of altitude and population density also emerges.